Characteristics of Chemotherapy Treatments for Breast Cancer Patients at Bhayangkara Tk.1 Pudsdokkes Polri Hospital, Jakarta - Febriani, Amelia; Pujiastuti, Fitria; Teodhora, Teodhora (Indonesian Journal of Cancer, 2024)
Background: Breast cancer is a malignant breast tumor that develops in the ductal or lobular epithelium and usually attacks women. Chemotherapy is a cornerstone of breast cancer treatment, particularly for patients with advanced disease or those who are not candidates for surgery or radiation therapy. This research aims to observe the use of chemotherapy drugs for breast cancer patients in terms of chemotherapy regimens and cycles at Bhayangkara Tk.1 Pudsdokkes Polri  Hospital. Methods: This study employs descriptive quantitative approaches. Data were gathered retrospectively from medical records of breast cancer patients receiving chemotherapy at Bhayangkara Tk.1 Pudsdokkes Polri  Hospital Jakarta from July to December 2021. Results: From 110 patients, 86 (78.18%) patients used the CAF regimen, 18 (16.36%) patients used the AC regimen, and 3 (2.73%) patients used the TAC regimen, while the regimen that did not comply with the guidelines was 2 (1.82%) patients using the combination of paclitaxel and epirubicin, 1 patient utilizing the combination of paclitaxel and doxorubicin. Forty-six (41.82%) patients with the CAF regimen had completed six cycles of chemotherapy with intervals of 3 weeks or 21 days, while only 5 patients (3.63%) completed four cycles of the AC regimen at 3-week or 21-day intervals. At the time of data collection, 11 patients, and 1 patient utilizing the AC regimen. This was because 59 patients had not yet finished the chemotherapy cycle, specifically in the advanced stage. Conclusions: The CAF regimen was the most commonly used chemotherapy regimen, followed by the AC and TAC regimens. This finding aligns with current clinical guidelines for breast cancer treatment. A significant number of patients had not yet completed their chemotherapy cycles, particularly those with advanced-stage breast cancer. This highlights the challenges associated with treating advanced disease and the need for more effective and less toxic treatment options.